Development of a mobile application for the sustainable management of coffee - José Luis Hernández Rodríguez; José Francisco Ramírez Dávila; Rodolfo Serrato Cuevas; Delfina de Jesús Pérez López; Federico Benjamín Galacho Jiménez (Pesquisa Agropecuária Tropical)
The coffee quality has been threatened by phytosanitary and nutritional problems, which have significantly reduced its production and yield. This study aimed to develop a mobile application that allows to create and manage plots using platforms such as Flutter for the front-end and Flask for the back-end, combined with geostatistical techniques to generate semivariograms, kriging and density maps, in order to estimate the spatial distribution and behaviour of a pest, as well as the spatial distribution of the primary macronutrients NPK, so that corrective actions can be taken at the right time, covering specific areas, and reducing environmental impacts, investment costs in fertilizers and pesticides, and helping to increase the coffee yield and quality.